Hubungan Kadar Hemoglobin dengan Prestasi Belajar Mahasiswi di Kampus Berbasis Pesantren - Kartika Pibriyanti; Umalasari Umalasari; Ladyamayu Pinasti; Lulu' Luthfiya (JURNAL RISET GIZI, 2025)
Background: Hemoglobin (Hb) played an important role in cognitive function and academic achievement. However, the direct association between Hb levels and student learning outcomes, particularly in Islamic boarding school–based campuses, has not been widely studied. Objective: This study aimed to analyze the relationship between hemoglobin levels and Cumulative Grade Point Average (GPA) as well as Pesantren Achievement Index (IPKS) among female students in a pesantren-based university. Methods: This was an observational analytic study with a cross-sectional approach involving 84 sixth-semester female students. Hb levels were measured using the EasyTouch GCHb device, while GPA and IPKS data were obtained from academic records. The Fisher Exact Test was used for statistical analysis. Results: Most respondents had normal hemoglobin levels (95.2%), good GPA (98.8%), and good IPKS (89.3%). No statistically significant relationship was found between Hb levels and GPA (p = 0.952) or IPKS (p = 0.055), although a practically relevant trend was observed in the IPKS results. Conclusion: There was no significant association between hemoglobin levels and student learning achievement as measured by GPA and IPKS. Academic and pesantren achievements were likely influenced by other factors beyond hemoglobin status, suggesting that intervention approaches should be multidimensional.